2015
DOI: 10.1016/j.radonc.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

A phantom assessment of achievable contouring concordance across multiple treatment planning systems

Abstract: In this paper, the highest level of inter-and intra-observer conformity achievable with different treatment planning systems (TPSs), contouring tools, shapes, and sites have been established for metrics including the Dice similarity coefficient (DICE) 2 AbstractIn this paper, metrics including the Dice similarity coefficient (DICE) and Hausdorff Distance determine the highest level of inter-and intra-observer conformity achievable with different treatment planning systems (TPSs), contouring tools, shapes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…The interobserver variation we found (median 95% Hausdorff of 4.3–5.1 mm) appears similar to those in [14] , where a maximum interobserver variation was found of 4.6 mm for MR based prostate delineation. Pogson et al [15] showed that interobserver variation in contouring increases with decreasing resolution, which is not what we found, however this study was CT based and considered delineation of inserts in a phantom, where no additional uncertainties are present. Since there was also no significant difference in volume between the different sequences, we conclude that all scans are in principle suitable for delineation of the prostate.…”
Section: Discussioncontrasting
confidence: 88%
“…The interobserver variation we found (median 95% Hausdorff of 4.3–5.1 mm) appears similar to those in [14] , where a maximum interobserver variation was found of 4.6 mm for MR based prostate delineation. Pogson et al [15] showed that interobserver variation in contouring increases with decreasing resolution, which is not what we found, however this study was CT based and considered delineation of inserts in a phantom, where no additional uncertainties are present. Since there was also no significant difference in volume between the different sequences, we conclude that all scans are in principle suitable for delineation of the prostate.…”
Section: Discussioncontrasting
confidence: 88%
“…(Mathworks Incorporated, Natick USA) platform, with a subset of metrics verified in MILXview to agree to within 2 significant figures, similarly to other reported values [26]. Generalized kappa (κ) statistics determine inter-observer delineation agreement which occurs by chance alone.…”
Section: Discussionmentioning
confidence: 60%
“…It has been well established that the main contouring discrepancies are at the medial and lateral edges of the WB CTV in supine imaging [31,32], however in prone datasets, geometrically these areas are reduced. Both intraobserver delineation variations [33] and differences due to planning system and data transfer [26] are much smaller than inter-observer variation and thus expected to have minimal impact on these WB results.…”
Section: Discussionmentioning
confidence: 99%
“…However by itself this is not enough. Imaging acquisition and reconstruction protocols should be specified in the methodology as these are known to affect volume delineation [144,145]. This particularly applies to the use of additional (non-CT) imaging datasets, usually not acquired within a radiation oncology department and susceptible to inter-scanner differences.…”
Section: Sample Size Detailsmentioning
confidence: 99%
“…In addition, results may vary according to the radiotherapy planning system used [147]. Pogson et al performed a phantom study on multiple planning systems and showed that concordance between them for delineated volumes can be very good, but is reduced with lower image resolution [144]. Single platform solutions are available although these have largely been used for training purposes [148].…”
Section: Metricsmentioning
confidence: 99%